2018
DOI: 10.3390/s18103450
|View full text |Cite
|
Sign up to set email alerts
|

Power Reduction with Sleep/Wake on Redundant Data (SWORD) in a Wireless Sensor Network for Energy-Efficient Precision Agriculture

Abstract: The use of wireless sensor networks (WSNs) in modern precision agriculture to monitor climate conditions and to provide agriculturalists with a considerable amount of useful information is currently being widely considered. However, WSNs exhibit several limitations when deployed in real-world applications. One of the challenges faced by WSNs is prolonging the life of sensor nodes. This challenge is the primary motivation for this work, in which we aim to further minimize the energy consumption of a wireless ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Tree (or cluster) networks combine multiple star networks. Both [ 61 ] and [ 178 ] implement a cluster network for monitoring crops. In [ 61 ] sensor nodes collect information from a crop and send messages to a router node.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tree (or cluster) networks combine multiple star networks. Both [ 61 ] and [ 178 ] implement a cluster network for monitoring crops. In [ 61 ] sensor nodes collect information from a crop and send messages to a router node.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although the power consumption is not an exclusive topic within the transport layer, according to [ 178 ] the highest power consumption for IoT devices within a WSN occur during the transmission of data. This review identified several approaches for optimizing the power consumption in IoT solutions for smart farming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Sensor layer, the proposed energy-saving approach is an on/off process which is based on the selection of a subset of nodes that will remain active for a certain period of time, while others remain inactive. Following this assumption, SWORD (sleep/wake on redundant data) is an energy preserving scheme that can be used to collect data on soil moisture [19]. The SWORD algorithm performs data control by removing redundant data so as to minimize energy consumption and increase the life of sensor nodes in the network.…”
Section: Energy-saving Technologiesmentioning
confidence: 99%
“…Equations (4) and (5) were used to estimate the total and average current drain by the proposed monitoring system. Consequently, the proposed system lifetime (L T ) could be determined based on Equation (6) [61].…”
Section: Power Consumption Modelmentioning
confidence: 99%